Aluminum Phosphide Poisoning, an Institutional Experience: Case Series - Basnet, Angela; Thapa, Ashok Jung; Khadka, Manoj; Regmi, Bishal; Khadka, Manita; Adhikari, Kabita; Thapa, Anil Jung; Shrestha, Dhan Bahadur (Journal of Nepal Health Research Council, 2022)
Background: The growing concern over pesticide use has been linked to self-harm and suicide especially in agricultural countries like Nepal. Pesticides like organophosphorus and aluminum phosphide cause the majority of deaths. Although organophosphorus poisoning is common means for suicide, Aluminum phosphide poisoning is also encountered occasionally. Our case series aims to look after the intent of poisoning and the outcome of the patients following Aluminum phosphide poisoning. Methods: This hospital record-based study includes Aluminum phosphide poisoning patients presenting to the emergency department of Scheer Memorial Adventist Hospital from first January 2017 to 31st December 2020. Data were analyzed using SPSS version-22. Results: Out of 25 total poisoning cases, most of them were female (60%) and married (56%). The case fatality rate was 84% among which 20% cases were brought dead while 64% died in the hospital. All poisoning cases were suicidal in intent. Conclusions: Herein we report a case series on 25 Aluminum phosphide poisoning cases with high case fatality rate and all cases being suicidal in intent. Keywords: Aluminum phosphide; Nepal; pesticides; suicide.